The Contagion Effect of Compensation Regulation: Evidence From China - Shao, Jun; Zhou, Haiyan; Gong, Na; Zhang, Junzi (Frontiers in Psychology, 2021)
To shed light on whether and how firms changed compensation practices in response to a shift in the environment in which they operated, we examine whether there is contagion effect of executive compensation regulation on state-owned enterprises (SOEs) in the emerging market of China. Specifically, we investigate whether firms not directly affected by the changing regulatory environment nonetheless changed executive compensation in response to the actions of the directly affected firms, which is called contagion effect. We further examine the specific contagion mechanisms and the economic consequences of regulation on compensation. We find that the regulation has a significant effect on compensation gap in central SOEs and a contagion effect on local SOEs but not for non SOEs. Within SOEs, there is an intra-industry contagion effect of compensation regulation but not an intra-region effect. Further, central SOEs and local SOEs experience reduced firm performance after the compensation regulations, but not the non-SOEs; indicating that the compensation regulation does not have favorable economic consequences for both the directly affected central SOEs and the indirectly affected local SOEs.